Comprehensive Structural, Electronic, and Biological Characterization of fac-[Re(CO)3(5,6-epoxy-5,6-dihydro-1,10-phenanthroline)Br]: X-Ray, Aromaticity, Electrochemistry, and HeLa Cell Viability - Morales-Guevara, R; Morales-Guevara, R (Multidisciplinary Digital Publishing Institute (MDPI), 2025)
The rhenium(I) tricarbonyl complex fac-[Re(CO)3(5,6-epoxy-5,6-dihydro-1,10-phenanthroline)Br] (ReL) has previously demonstrated promising luminescent properties, enabling its direct application as a probe for walled cells such as Candida albicans and Salmonella enterica. In this new study, we present a significantly expanded and comprehensive characterization of ReL, incorporating a wide range of experimental and computational techniques not previously reported. These include variable-temperature 1H and 13C NMR spectroscopy, CH-COSY, single-crystal X-ray diffraction, Hirshfeld surface analysis, DFT calculations, Fukui functions, non-covalent interaction (NCI) indices, and electrochemical profiling. Structural analysis confirmed a pseudo-octahedral geometry with the bromide ligand positioned cis to the epoxy group. NMR data revealed the coexistence of cis and trans isomers in solution, with the trans form being slightly more stable. DFT calculations and aromaticity descriptors indicated minimal electronic differences between isomers, supporting their unified treatment in subsequent analyses. Electrochemical studies revealed two oxidation and two reduction events, consistent with ECE and EEC mechanisms, including a Re(I) -> Re(0) transition at -1.50 V vs. SCE. Theoretical redox potentials showed strong agreement with experimental data. Biological assays revealed a dose-dependent cytotoxic effect on HeLa cells, contrasting with previously reported low toxicity in microbial systems. These findings, combined with ReL s luminescent and antimicrobial properties, underscore its multifunctional nature and highlight its potential as a bioactive and imaging agent for advanced therapeutic and microbiological applications.